TECHNICAL ASPECTS OF A NEW METHOD OF SURGICAL TREATMENT OF COMPLICATED ECHINOCOCCOSIS OF THE LUNGS - Akhmedova, N.A.; Kurbonkulov, A.A (Educational Research in Universal Sciences, 2023)
Despite significant progress in the treatment of echinococcosis of the lungs (EL), there are still controversial issues of choosing a method of surgical intervention for complicated and giant cysts. The purpose of the study. To development of a method of surgical treatment of complicated EL. Material and methods. The objective of these studies was to develop an experimental model of lung lobe resection against the background of microbial contamination. Experimental studies were carried out in the laboratory of experimental surgery of the State Institution "RSSPMCS named after academician V. Vakhidov" from 2021 to 2022. Results. When performing lung resection by the type of lobectomy, almost all rats received a small amount of air through the puncture sites of the lungs, even with the use of atraumatic needles 4/o and the use of U-shaped sutures. Conclusion. For practical thoracic surgery, a method of surgical treatment of giant infected echinococcal lung cysts is proposed, which consists in performing anatomical resection of the lung with manual suturing of the bronchus stump according to the proposed scheme, followed by local laser exposure and application of a powdered Hemoben composition to the wound surface of the lung and bronchus stump.